Help-seeking behaviour and associated factors among women who experienced physical and sexual violence in Ethiopia: evidence from the 2016 Ethiopia Demographic and Health Survey - Simegnew Handebo; Ayenew Kassie; Adane Nigusie (BMC, 2021)
Abstract Background Violence against women remains devastatingly pervasive and remained unchanged over the past decade. Violence against women is preventable and help-seeking of women subjected to violence is an entry point. So, this study assessed help-seeking behaviour and associated factors among women who experienced physical and sexual violence in Ethiopia. Method Using the 2016 Ethiopia Demographic and Health Surveys (EDHS), this paper analyzes the determinants of help-seeking behavior of women subjected to violence in Ethiopia. EDHS used a two-stage stratified cluster sampling technique. From 642 communities, a total of 1540 (weighted) reproductive age women were included in the analysis. Simple descriptive, bivariable and multivariable logistic regression analysis were employed. Statistical significance was set at a p-value of less than 0.05. Results Only 22.5% of the women who experienced violence sought help. Being aged 30 and above, working in sales, or an agricultural job, being in the richest wealth quintile, and experiencing severe violence were associated with increased help-seeking behaviour. Living in a rural area, having a husband who attended primary, secondary, and higher education, having a husband working in a professional job and agriculture were factors associated with lower odds of help-seeking behaviour. Conclusion In Ethiopia below one-fourth of women who were subject to violence sought help. Socio-demographic factors and severity of the violence were associated with help-seeking. Preventing child marriages and reducing poverty as well as increased employment and education for women enhance help-seeking behaviour by the women. Interventions could include creating awareness, law enforcement, and support for victims.